1998
DOI: 10.1164/ajrccm.157.1.9701010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abdominal Strapping on Forced Expiration in Tetraplegic Patients

Abstract: Patients with traumatic transection of the lower segments of the cervical cord contract the clavicular portion of the pectoralis major during forced expiration and cough, and the rise in intrathoracic pressure resulting from this contraction produces dynamic airway compression in many patients. Because the abdominal muscles are paralyzed, however, there is paradoxical expansion of the abdomen, which may reduce the rise in intrathoracic pressure and the degree of airway collapse. To evaluate the magnitude of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 11 publications
3
37
0
Order By: Relevance
“…Consistent with previous findings, [8][9][10] we found that the use of an AB significantly increased VC. The binder causes a decrease in RV and FRC because the diaphragm is pushed in the cranial direction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous findings, [8][9][10] we found that the use of an AB significantly increased VC. The binder causes a decrease in RV and FRC because the diaphragm is pushed in the cranial direction.…”
Section: Discussionsupporting
confidence: 93%
“…It is well documented that one effect of binding is to increase vital capacity (VC). [8][9][10] As VC is reduced in SCL persons to approximately 50-60% of reference values, it seems reasonable to conclude that increases in VC are beneficial. 7,11,12 The potentially beneficial effect of an abdominal binder (AB) may, however, be related to the achieved maximal lung expansion, that is, to total lung capacity (TLC) rather than VC.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Nevertheless, constantly applied pressure and positioning cannot produce forced expiration or coughing, which is necessary for efficient removal of secretions and solid particles from the respiratory tracts. 7 Impairment of coughing may cause bronchial obstruction and consequent atelectasis pneumonia with severe respiratory disturbances. 1 Caregivers believe that these can be prevented if the patient's cough is assisted by intermittently applied artificial pressure to the abdomen.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] A few studies that focus on improving cough ability among persons with SCI have been conducted. These include studies on therapeutic manoeuvres, 7 use of abdominal binders, [8][9][10][11][12][13] the use of electrical stimulator 14,15 and functional magnetic stimulator. 16,17 Studies by Jaeger et al 7 and Linder 15 found that cough efficacy produced by electrical stimulation was as effective as manually assisted cough in subjects with tetraplegia.…”
Section: Introductionmentioning
confidence: 99%
“…13 Variables such as demographics of subjects, type of abdominal binders and respiratory outcome parameters in previous studies on the use of the abdominal binder were not well controlled, thus making the use of abdominal binders in SCI unclear. [9][10][11]13 As there is evidence that abdominal binders may be useful for SCI patients, [10][11]13 we chose to explore the effectiveness of different types of elastic abdominal binders (single-strap versus triple-strap abdominal binder) and their methods of application.…”
Section: Introductionmentioning
confidence: 99%